Participation Rate of Employees of RS X In The Covid-19 Vaccination Program to Break The Chain The Spread of Covid-19 - Kristianto Kristianto (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2021)
The COVID-19 vaccination aims to reduce the transmission of COVID-19, reduce morbidity and mortality due to COVID-19, achieve herd immunity, and protect the community from COVID-19 to remain socially and economically productive. The role of social media in the era of digital technology can bring positive things as well as negative things, in a positive context there are invitations in the form of motivation to participate in vaccination programs. Meanwhile, in a negative context, the COVID-19 vaccination has become a cornering or scary hoax. However, this news cannot be verified. However, this news greatly influences a person's decision to participate or not in the vaccination program in addition to doubts about the safety of vaccines, doubts about the effectiveness of vaccines, distrust of vaccines, fears of side effects such as fever and pain, and religious reasons. This study will explain the level of participation of workers who work in Hospital X in receiving a prioritized vaccination program for health workers. The research method used is descriptive, where data is collected in the period from January 29, 2021, to May 10, 2021. The vaccination program which is an alternative to breaking the chain of the spread of COVID-19 is welcomed by its implementation in Hospital X with the participation rate of the results. reached 92%. The remaining 8% were not vaccinated because they did not receive a recommendation from a doctor or refused the vaccine because they were worried about the side effects.